PETROLOGY OF FORSTERITE-CLINOHUMITE MARBLES OF THE VORONEZH CRYSTALLINE MASSIF - Savko K.A.; Skryabin V.Y. (My University, 1999)
Clinohumite-bearing parageneses Cal + Dol + Chu 4- Fo + Tr + Phi, Cdl + Dol + Chu + Fo + Phi, Cal + Dol + Chu + Sp, and Cal + Chu + PI + Qtz, referred to the progressive stage of regional metamorphism, have been revealed in the Archean marbles of the Voronezh Crystalline Massif (VCM). Clinohumite-forsterite-calcite-dolomite equilibria are poorly studied compared with other aspects of mctamorphism of carbonate rocks with H2O-CO2-HF fluid phase. In the presence of this fluid phase metamorphic paragcneses differ from ordinary well-studied mineral assemblages 0Г magnesian marbles and are stable in a narrow range of /'-T-Xcoj-Conditions, characterized by a low CO2 activity in the fluid, low and moderate pressures, and temperatures of 500-750 °C. Analysis of the T-XcOi phase diagrams of the studied clinohumite-bearing parageneses permitted determination of Хсог (0.08) and the temperature range of their stability (500-700 °C) at P = 5 kbar. The composition of the fluid phase was completely or partly buffered by metamorphic reactions.
Keywords: MAGNESIAN MARBLES; CLINOHUMILE; FORSTERIIE; FLUID PHASE; BUFFERING